Financial Feasibility Study of Middlemist Florist for Expansion - Lorensia Christina; Subiakto Subiakto; Achmad Herlanto Anggono (Dinasti Research, 2025)
his study aims to evaluate the feasibility of Middlemist Florist’s business expansion by opening three new booths in strategic locations in Indonesia. Middlemist, as a leading player in the florist industry, has been operating since 2021, offering various fresh flower arrangements with exclusive designs. However, in the face of increasing competition, Middlemist needs to develop innovative business strategies to enhance revenue and expand its market reach. Using a quantitative approach, this study assesses the financial feasibility of Middlemist’s expansion by analyzing financial reports from 2021 to 2024, including income statements, balance sheets, and cash flow statements. Financial projections for the next five years were conducted to evaluate feasibility using methods such as Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period. The analysis revealed that the expansion project’s NPV is IDR 32.7 million, with an IRR of 66.52%, significantly exceeding the Weighted Average Cost of Capital (WACC) of 6.78%. Additionally, the PI value of 3.18 indicates substantial financial benefits compared to the initial investment cost. The Payback Period is estimated at only 1 year and 6 months, reflecting the efficiency and short-term profitability of this expansion. Sales projections indicate potential annual revenue of IDR 51.6 million per booth, with an average monthly sales target of IDR 4.3 million. This success relies heavily on Middlemist’s ability to capitalize on seasonal trends and customer demand for high-quality flower arrangements. However, the main challenges include competing with other florist businesses and maintaining high standards of quality and product innovation. This study recommends that Middlemist enhance its marketing strategies through digital approaches and collaborations with event organizers to expand its customer base. Revenue from the new booths should also be allocated to strengthening the operations of the main store and diversifying products to reach a broader market segment. Additionally, Middlemist should ensure sustainable operations by prioritizing environmentally friendly flower sourcing and supporting local farmers, aligning with the company’s vision. These findings suggest that expansion into three strategic locations not only has the potential to increase revenue but also strengthens Middlemist’s position in the growing florist industry in Indonesia. This study provides practical contributions to data-driven business strategy development, focusing on financial efficiency and business sustainability. This expansion is expected to be the first step in realizing Middlemist’s vision of being a premium flower provider that brings beauty and meaning to every important customer moment.